Machiavellianism A synthesis of the evolutionary and psychological literatures. [article]. - Wilson, David Sloan
Manipulative strategies of social conduct (Machiavellianism) have been studied by both psychologists and evolutionary biologists. The authors use the psychological literature as a database to test evolutionary hypotheses about the adaptive advantages of manipulative social behavior. Machiavellianism does not correlate with general intelligence and does not consistently lead to real-world success. It is best regarded as 1 of several social strategies, broadly similar to the "defect" strategy of evolutionary game theory, which is successful in some situations but not in others. In general, human evolutionary psychology and evolutionary game theory provide useful frameworks for thinking about behavioral strategies, such as Machiavellianism, and identify a large number of specific hypotheses that have not yet been tested by personality and social psychologists. -- (from the author)